Application of DeVito’s Interpersonal Communication By Frontliner In Resolving Customer Complaints At PT. Bank Syariah Indonesia Bengkulu Branch Office - Astina, Melni Dwi; Saragih, Rasi; Sari, Eka Vuspa (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
This study aims to analyze the application of the principles of interpersonal communication by DeVito frotliner in handling customer complaints at PT. Bank Syariah Indonesia Bengkulu Branch Office. The research method used is a qualitative method with a phenomenological approach. Research data obtained through observation ,interviews and documentation. There were 7 informants in this study consisting of 7 main informants and 4 key informants. The technique for determining informants was by purposive sampling with the criteria set by the researcher. The results of this study indicate that from the aspect of Openness, interpersonal communication between frontliner and customers. This can be seen from the way he listens to complaints openly and reacts honestly. From the principle of Empathy, seen from ability frontliner in calming customers and focusing on customer complaints. For the principle of Support, visible from the ability frontliner respecting customer explanations to the end and trying to find the best solution to customer complaints. Furthermore, from the principle of Equality, seen from the attitude frontliner provide comfortable interactions with customers